The Impact Of Internet Marketing Strategy On Customer Relationship Quality And Firmâs Marketing Competency Of Aceh Smeâs - Madjid, Iskandarsyah; Syahnuri, Muhammad (JOURNAL OF ECONOMIC SCIENCE, 2015)
Along with the rising of information technology, business competition has caused many phenomena and new strategies in the marketing world. Those conditions require businesses to be more careful about conducting marketing strategy in maintaining their business. It takes a new marketing strategy and innovative in improving the marketing and sales of the company itself. So that it can compete with the competitors. The purpose of this study was to determine the extent of use of the Internet as a marketing strategy by the entrepreneurs who run their business in Aceh. Data collection is done by sending the questionnaires to questionnaires to CEOâs Small Business Firms in Aceh, both online and offline. Measurements of constructs both the validity and reliability use the Hierarchical Linear Modeling regression analysis to test the hypotheses relationship and estimate factors affecting the Firmâs. The results of this study show the effect of the internet implementation strategy of the customer relationship quality and its impact on firmâs marketing competency in Aceh.